Enalapril maleate orally disintegrating tablets: tableting and in vivo evaluation in hypertensive rats. (28th May 2018) - Tawfeek, Hesham M.; Faisal, Waleed; Soliman, Ghareb M.
Abstract: The aim of this study was to develop orally disintegrating tablets (ODTs) for enalapril maleate (EnM) to facilitate its administration to the elderly or other patients having dysphagia. Compatibility between EnM and various excipients was studied using differential scanning calorimetry. ODTs of EnM were prepared by direct compression of EnM mixtures with various superdisintegrants. The tablets were evaluated for physical properties including drug content, hardness, friability, disintegration time, wetting time, and drug release. The antihypertensive effect of the optimum EnM ODTs was evaluated in vivo in hypertensive rats and compared with commercial EnM formulation. EnM ODTs had satisfactory results in terms of drug content and friability. Tablet wetting and disintegration were fast and dependent on the used superdisintegrant where croscarmellose showed the fastest wetting and disintegration time of ∼7 s. EnM release from the tablets was rapid where complete release was obtained in 10–15 min. Selected EnM ODTs rapidly and efficiently reduced the rat's blood pressure to its normal value within 1 h, compared with 4 h for EnM commercial formulation. These results confirm that EnM ODTs could find application in the management of hypertension in the elderly or other patients having dysphagia.